2016
DOI: 10.1002/lary.26139
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of nodal failure after intensity modulated radiotherapy for nasopharyngeal carcinoma

Abstract: 4. Laryngoscope, 2016 127:377-382, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
(47 reference statements)
1
20
0
Order By: Relevance
“…Kong et al 21 analyzed 370 non-metastatic NPC patients treated with IMRT (with or without chemotherapy) and found regional relapses in 11 patients, of which 81.8% (9/11) were in-field. With a median follow-up of 70.4 months, 6.0% (10/165) of patients with NPC who had been treated with IMRT developed nodal relapse, and in-field failures accounted for 60% of all nodal failures, as reported by Li et al 18 . The authors also demonstrated agreement between the phenomenon that most in-field failures occurred in level II and the distribution of pretreatment nodes in patients with NPC, as level II was the most frequently involved nodal group.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Kong et al 21 analyzed 370 non-metastatic NPC patients treated with IMRT (with or without chemotherapy) and found regional relapses in 11 patients, of which 81.8% (9/11) were in-field. With a median follow-up of 70.4 months, 6.0% (10/165) of patients with NPC who had been treated with IMRT developed nodal relapse, and in-field failures accounted for 60% of all nodal failures, as reported by Li et al 18 . The authors also demonstrated agreement between the phenomenon that most in-field failures occurred in level II and the distribution of pretreatment nodes in patients with NPC, as level II was the most frequently involved nodal group.…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, regional control is a major concern in NPC treatment. Li et al 18 reported that 75% of their NPC patients had involved lymph nodes, and 7.7% eventually underwent recurrence after treatment. A total of 84.7% (233/275) of the patients in our study presented with lymphadenopathy at the time of diagnosis, and only 6.2% (17/275) of the patients developed regional failure at a median follow-up time of 71 months.…”
Section: Discussionmentioning
confidence: 99%
“…IMRT produces more accurate dose homogeneity around targets and less toxicity to normal organs than CRT. [2] The advantages of IMRT to spare the parotid gland have been demonstrated repeatedly, and its use for NPC was more prevailed than CRT. [2,3] However, results showing that IMRT in terms of oncologic outcomes had limited success compared with CRT, and most results were only come from China or other Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…[2] The advantages of IMRT to spare the parotid gland have been demonstrated repeatedly, and its use for NPC was more prevailed than CRT. [2,3] However, results showing that IMRT in terms of oncologic outcomes had limited success compared with CRT, and most results were only come from China or other Asian countries. [46] For the time being, there is no undisputed evidence that IMRT is superior to CRT regarding overall survival, locoregional control, disease-free survival, and metastasis-free survival.…”
Section: Introductionmentioning
confidence: 99%
“…Local control rate of NPC has improved markedly in the past decade (3). However, local recurrence and metastasis remain the primary causes of mortality from this cancer, particularly in advanced stages (4), and management of local treatment failure remains a challenge in NPC treatment.…”
Section: Introductionmentioning
confidence: 99%